Conservation of threatened birds inhabiting over Pantanos de Villa, Lima, Peru - Pulido Capurro, Víctor (2020)
In the Wildlife Refuge Villa Swamps located in the central coast on an area of 263.27 ha, there were 211 species of birds of which officially 19 species are categorized as threatened. The current state of the conservation of threatened bird species, the range of dis- tribution and the trend of relationships are described, as well as the importance of the ha- bits of the Villa Swamps as a place of refuge and conservation of the species in Peru.